2022
DOI: 10.3390/s22031276
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Transparent Circularly Polarized Patch Antenna for Reliable Unobtrusive Wearable Wireless Communications

Abstract: This paper presents a circularly polarized flexible and transparent circular patch antenna suitable for body-worn wireless-communications. Circular polarization is highly beneficial in wearable wireless communications, where antennas, as a key component of the RF front-end, operate in dynamic environments, such as the human body. The demonstrated antenna is realized with highly flexible, robust and transparent conductive-fabric-polymer composite. The performance of the explored flexible-transparent antenna is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 52 publications
(76 reference statements)
0
18
0
Order By: Relevance
“…Our three-layer standard body model has a volume of (skin = 4, fat = 8, muscle = 30, and air layer under the tissue layers = 8 (in mm)) and the four-layer phantom model has the volume of (skin = 2, fat = 8, muscle = 40, bone = 30, and air layer under the tissue layers = 8 (in mm)). The performance of the designed BSA device was evaluated for different tissue layer morphologies as well as spacing from the phantom model, according to the standard methods discussed in [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our three-layer standard body model has a volume of (skin = 4, fat = 8, muscle = 30, and air layer under the tissue layers = 8 (in mm)) and the four-layer phantom model has the volume of (skin = 2, fat = 8, muscle = 40, bone = 30, and air layer under the tissue layers = 8 (in mm)). The performance of the designed BSA device was evaluated for different tissue layer morphologies as well as spacing from the phantom model, according to the standard methods discussed in [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The muscle layer has an ε r of 52.7 and 48.2 and a of 1.95 S/m and 6.0 S/m at the lower and upper-frequency bands, respectively. The bone layer has an ε r of and a 11.4 of 0.39 S/m, and of 9.674 and 1.1544 S/m at 2.45 and 5.8 GHz in the lower and upper frequencies, respectively [ 55 , 56 , 57 , 58 ]. For modeling the arm, a simple layered cylindrical model was utilized.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the research of textile circularly polarized antennas dominantly covers flexible and transparent antennas for reliable wearable applications [ 27 ], conformal textile antenna arrays for wearable devices [ 28 ], UWB antennas for body-centric communication [ 19 ], and multiple-input multiple-output one [ 29 ]. In all those emerging concepts, the fundamental principles presented in this paper can be applied to move the operation frequency of textile-integrated radiators higher.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in order to estimate the applicability of antennas for body-worn wireless devices, the antenna parameters and characteristics need to be studied both in free space and on the human body [ 4 ]. Several types of flexible wearable antennas for embedding into garments or accessories have been presented that fully or partially meet the design requirements: patch antennas [ 5 , 6 , 7 , 8 , 9 , 10 ], textile slotted waveguide antennas [ 11 ], monopole textile antennas [ 12 , 13 ], and fully-textile loop antennas [ 14 , 15 ]. The effects of the human body on antenna parameters and characteristics has been numerically investigated by employing homogenous (cylindrical [ 11 ], rectangular [ 11 , 14 ], forearm [ 5 ], full-scale human body model [ 7 ]) and multilayer (cylindrical [ 6 ], rectangular [ 15 ]) human body models.…”
Section: Introductionmentioning
confidence: 99%
“…The SAR limits for local exposures in the considered frequency range were established in recent ICNIRP guidelines and IEEE C95.1-2019 standard [ 17 , 19 ]. Several previously reported works on fully textile and optically transparent wearable antennas showed that the simulated peak 1 g and 10 g average SAR generated from the antennas in a homogeneous flat phantom [ 14 ], in the chest, upper arm, and the wrist of the HUGO human body model [ 7 ], in a multilayer cylindrical human body model [ 6 ] and in a forearm phantom [ 5 ] varied from 0.22 to 0.533 W/kg (SAR 1 g) and from 0.148 to 0.695 W/kg (SAR 10 g), at 2.45 GHz at a net input power of 100 mW.…”
Section: Introductionmentioning
confidence: 99%